밤의 농작물 재해보험 도입을 위한 기초연구 - 석현덕 (한국농촌경제연구원, 2004)
Crop insurance, one measure to counter natural disasters, is the most superior system preserving income from accidents. Insurance system has been currently introduced into six agricultural products including apples, and pears. Chestnuts, however, have not been seriously discussed for the object of crop insurance before a series of typhoons resulted in decreasing outputs. The purpose of this study is estimating standard yield table, appraising damage from disasters, preparing incentives for inducing producers, and suggesting a program for an exhibition application. The demand for the insurance has been estimated that about 6~20% of total chestnut farmers would insure. Standard yield tables vary between areas, and the yield and the age of chestnut trees have no significant relationship. The reason is that methods of plantation and caring are not standardized, and are different from region to region. To apply the standard yield tables into the main insurance business, it is required to improve the tables. The appraisal system currently used for crop insurance will be directly applied for chestnuts. It is reasonable to entrust Forestry Cooperatives with field investigation for making good use of the experienced. It takes probably three years to introduce main crop insurance system into chestnut. Preparation for the exhibition application requires a year, and exhibition application needs at least two years.